2020
DOI: 10.1007/s00109-020-01924-9
|View full text |Cite|
|
Sign up to set email alerts
|

Local Wnt3a treatment restores bone regeneration in large osseous defects after surgical debridement of osteomyelitis

Abstract: Impaired bone homeostasis caused by osteomyelitis provokes serious variations in the bone remodeling process, thereby involving multiple inflammatory cytokines to activate bone healing. We have previously established a mouse model for post-traumatic osteomyelitis and studied bone regeneration after sufficient debridement. Moreover, we could further characterize the postinfectious inflammatory state of bony defects after debridement with elevated osteoclasts and decreased bone formation despite the absence of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…Finally, many other biomarkers, such as IL-6, retinol-binding protein, prealbumin, and PSP, among others, have been studied with contradictory evidence and no clear practical usefulness [ 1 , 11 , 22 , 24 ]. The expression of DKK1 has been recently evaluated in the context of osteomyelitis [ 39 ] and infectious processes [ 40 - 42 ] but as far as we know, there exist no reports of spinal infections. We include this marker in the systematic review to confirm that there exist no previous studies in this respect as to establish a starting point for a research line in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, many other biomarkers, such as IL-6, retinol-binding protein, prealbumin, and PSP, among others, have been studied with contradictory evidence and no clear practical usefulness [ 1 , 11 , 22 , 24 ]. The expression of DKK1 has been recently evaluated in the context of osteomyelitis [ 39 ] and infectious processes [ 40 - 42 ] but as far as we know, there exist no reports of spinal infections. We include this marker in the systematic review to confirm that there exist no previous studies in this respect as to establish a starting point for a research line in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…Mice of the uninjured bone group did not receive any operation. Euthanasia was performed by cervical dislocation according to national and international laws and guidelines d3 and d7 postoperation, which represents an early and late time point during bone regeneration 15,16 . Each group consisted of at least five animals.…”
Section: Methodsmentioning
confidence: 99%
“…However, the use of Wnt/β-catenin inhibitors, such as Quercitin, reduce MSC proliferation and multipotency by favoring their osteogenic commitment and inhibiting both the chondrogenic and the adipogenic differentiation (Qu et al, 2013;Narcisi et al, 2015;Jothimani et al, 2020;Volleman et al, 2020). This model failed to explain the positive contribution of canonical Wnt in bone homeostasis in vivo (Wagner et al, 2020). Liu et al suggested a role for Wnt/β-catenin activation levels; in fact, they observed a promoting effect with low concentrations of Wnt3a during osteogenic differentiation, through the regulation of key transcription factors such as RUNX2 and Osterix (Osx), while higher concentrations suppressed both osteogenesis and adipogenesis (Gaur et al, 2005;Liu et al, 2009).…”
Section: The Wnt Signaling In Mscsmentioning
confidence: 99%